Learning Strategies in Physical Education to Improve Physical Fitness: Systematic Literature Review (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Physical fitness plays a vital role in supporting the physical development, cognitive growth, and healthy lifestyle habits of elementary school students. Nevertheless, the delivery of physical education (PE) in many schools remains predominantly conventional, often emphasising routine exercises and lacking innovative pedagogical strategies that effectively stimulate fitness improvement. This study aims to identify evidence-based learning models that significantly improve students’ physical fitness through a systematic literature review (SLR). The research utilised the PICO framework (Population, Intervention, Comparison, Outcome) and adhered to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Relevant articles were retrieved using the Publish or Perish application from databases such as Google Scholar and Crossref, employing keywords including “student physical fitness,” “physical education learning models,” and “teaching style in physical education.” From an initial pool of 1,000 articles published in the last 10 years, seven met the defined inclusion and exclusion criteria. The findings indicate that innovative instructional models such as Project-Based Learning (PjBL), circuit games, Puzzle Run, and play-based approaches are effective in improving cardiovascular endurance, muscular strength, agility, and motor coordination. These active and contextual strategies contrast significantly with traditional teacher-centred approaches, providing more engaging and meaningful physical learning experiences. The review concludes that applying learner-centred, playful, and integrated teaching models in physical education can better facilitate the development of comprehensive physical fitness among elementary students.